A Preliminary Study Of Differentially Expressed Genes In Malaysian Colorectal Carcinoma Cases - Ui, Edmund Hang Sim; Bong, Ivyna Pau Ni; Jamal, Rahman; Nadeson, Sukumar; Balraj, Pauline; Tan, S.K.; Sagap, I; Rose, I.M.; Lim, P.K.M (Universiti Sains Malaysia, 2006)
Presently, the complete genetic mechanisms for the progression of adenoma to carcinoma for colorectal carcinoma (CRC) remain largely unclear. In order to obtain genetic information of this cancer pathway, we searched for differentially expressed genes in tumours of CRC. Gene expression profiles from CRC cases were assessed via the DNA microarray system. We report up-regulation and down-regulation of 819 and 98 genes respectively, in the tumours relative to their normal controls. The differential expression patterns of 121 genes were persistent in all tumours. Thirty three of these are ribosomal proteins (RPs) genes. Comparison of the 121 genes with a public domain gene expression database, the Cancer Gene Expression Database (CGEP), revealed 47 genes to be consistently differentially expressed in colorectal tumours. Among these, 22 are RP genes. Among all RP genes identified in this study the over-expression pattern for six of them is consistent with literature. The up-regulation of RP L32 in CRC tumours was demonstrated for the first time in this study and it was also verified via reverse transcription-polymerase chain reaction (RT-PCR) analysis. Non-RP genes worth noting are the tumour susceptibility gene (TSG101) and the 20-kDa myosin light chain (MLC-2). Albeit small sample size (n = 2 for microarray analysis), our preliminary studies revealed many genes that are brought into the context of CRC tumourigenesis for the first time, thus providing new clues to the genetic events during colorectal carcinogenesis.